Towards a Framework for the Industrial Recommissioning of Residual Energy (IRRE): How to Systematically Evaluate and Reclaim Waste Energy in Manufacturing - Jannis Eckhoff; Vincent Adomat; Christian Kober; Marc Fette; Robert Weidner; Jens P. Wulfsberg (Machines)
The extensive body of research dedicated to optimizing energy consumption and efficiency in the manufacturing sector demonstrates a significant and well-established legacy. Despite a peak of publications in this field over recent years, the subject of reusing residual energy is only infrequently discussed. Where authors target this topic, research is often exclusively directed towards specialized applications or industries. In this article, an initial attempt of approaching residual energy reclamation in industrial manufacturing in a structured and universal manner is made. By employing a systematic literature review and design science research, a universal tool chain for decomposing individual industrial manufacturing systems to successfully reclaim and reintegrate residual energy is developed. A comprehensive overview of technologies available for energy conversion in industrial scenarios and their corresponding efficiency ranges are presented in the form of a table, called the energy conversion overview (ECO) table. The main contribution poses a multistep sequential framework guiding through identifying, assessing, harnessing, reusing, and validating residual energy in manufacturing systems. As a universal tool, the Industrial Recommissioning of Residual Energy (IRRE) framework is empowering its adopters to systematically approach residual energy recovery in their individual context by a universal tool. The application of both tools is showcased in a case study from the large-aircraft carbon fiber manufacturing industry.